Antibacterial Activity of Fistulin: A Protease Inhibitor Purified from the Leaves of Cassia fistula. (20th June 2012) - Arulpandi, I.; Sangeetha, R.
Abstract : Plant protease inhibitors (PPIs) are one of the important components of a plant's defense machinery. PPIs are active against the insects and microbes which invade the plant. Cassia species possess anti-insecticidal and antimicrobial properties and this study was aimed at investigating the antibacterial efficacy of a PPI present in the leaves of Cassia fistula . A PPI, fistulin, was isolated from the leaves of C. fistula and purified by gel filtration chromatography. The antibacterial activity of the purified fistulin was studied against five bacterial strains, namely, Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli . The PPI was found to be very active against S. aureus, E. coli, B. subtilis, and K. pneumonia, and its efficacy was comparable to the standard drug, streptomycin sulphate.